Second generation swimming feedback device using a wearable data processing system based on underwater visible light communication - Hagema, R. M.; Haelsig, T.; O`Keefe, S. G.; Stamm, A.; Fickenscher, T.; Thiel, D. V. (Procedia Engineering, 2013)
Swimmers performance evaluation is important for the swimmers, their coaches and trainers. Most systems depend on visual, video processing or sensors and require post processing to obtain the swim data. Stroke rate, stroke length and swim velocity data are useful parameters for a swimmer during a swim. Swimmers can then adjust their swim to achieve optimal performance. A wearable data processing system was designed, implemented and tested using visible light communication. A wrist-mounted accelerometer with a communications link to a receiver located on the goggles allows visual information to be given to the athlete. This helps swimmers to swim with consistent pace based on a multi-coloured display. The data processing system was based on a circular buffer to read real time acceleration data. The maximum acceleration and the position of the maximum acceleration during one stroke are determined in firmware. The time difference between strokes is transmitted to the goggles. An algorithm at the receiver uses the data to switch on the LED colour so that the swimmer reacts according to previous instructions. The second generation system (size 35 x 35 mm, cost $19.89AU) was designed and implemented. The system was tested with different swim speeds (slow and fast) and different strokes (free style, back stroke, breast stroke and butterfly) to validate the system. These experiments were used to optimise the system and verify that the complete system is viable under different conditions, styles and swimmers.